2013
DOI: 10.3171/2013.6.spine12655
|View full text |Cite
|
Sign up to set email alerts
|

The effect of screw head design on rod derotation in the correction of thoracolumbar spinal deformity

Abstract: Object. The use of fixed-axis pedicle screws for correction of thoracolumbar deformity in adult surgery is demanding because of the challenge of assembling the bent rod to the screw in order to achieve curve correction. Polyaxial screw designs, providing increased degrees of freedom at the screw-rod interface, were reported to be insufficient in achieving correction of thoracic deformity in the axial plane. Using a multisegment bovine calf spine model, this study investigated the ability of a new uniplanar scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Many biomechanical studies demonstrated that the designs of the screw head play a significant role in the correction of spinal deformity and have different effects on the stiffness in three dimensions (coronal, sagittal, and axial plane) [17]. An experimental study reported by Wang showed that the mono-axial pedicle screw with no motion between the screw head and shaft can significantly increase the stiffness in the axial direction compared with the poly-axial pedicle screw and can reduce the risks of correction loss [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many biomechanical studies demonstrated that the designs of the screw head play a significant role in the correction of spinal deformity and have different effects on the stiffness in three dimensions (coronal, sagittal, and axial plane) [17]. An experimental study reported by Wang showed that the mono-axial pedicle screw with no motion between the screw head and shaft can significantly increase the stiffness in the axial direction compared with the poly-axial pedicle screw and can reduce the risks of correction loss [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a transpedicular screw is popularly used to treat thoracolumbar burst fractures. Many biomechanical studies demonstrate that the designs of the screw head play a significant role in the correction of spinal deformity and have different effects on the stiffness in three dimensions (coronal, sagittal, and axial plane) [17].…”
Section: Introductionmentioning
confidence: 99%
“…11 Many biomechanical studies demonstrate that the designs of screw head play a signi cant role in the correction of spinal deformity and have different effects on the stiffness in three dimensions (coronal, sagittal, and axial plane). 16 An experimental study has reported by Wang that the mono axial pedicle screw with no motion between screw head and shaft can signi cantly increase the stiffness in axial direction compared with poly axial pedicle screw, and reduce the risks of correction loss. 29 Mono axial pedicle screws can be a better xation instrumentation for thoracolumbar burst fractures in theory.…”
Section: Discussionmentioning
confidence: 99%
“…Many biomechanical studies demonstrate that the designs of screw head play a signi cant role in the correction of spinal deformity and have different effects on the stiffness in three dimensions (coronal, sagittal, and axial plane). 16 According to biomechanical theory, the mono axial pedicle screw could, more effectively than the poly axial pedicle screws, restore the vertebral height, correct the kyphosis, reduce the postoperative kyphosis loss, and maintain fracture reduction.…”
Section: Introductionmentioning
confidence: 99%